Carbon-based interlayers in perovskite solar cells. (May 2020) - Litvin, Aleksandr P.; Zhang, Xiaoyu; Berwick, Kevin; Fedorov, Anatoly V.; Zheng, Weitao; Baranov, Alexander V.
Abstract: Perovskites are solution-processed, high-performance semiconductors of interest in low-cost photovoltaics. The interfaces between the perovskite photoactive layers and the top and bottom contacts are crucial for efficient charge transport and minimizing trapping. Control of the collection of charge carriers at these interfaces is decisive to device performance. Here, we review recent progress in the realization of efficient perovskite solar cells using cheap, easily processed, stable, carbon-based interlayers. Interface materials including graphene, carbon nanotubes, fullerenes, graphene quantum dots and carbon dots are introduced and their influence on device performance is discussed. Highlights: The use of carbon nanomaterials in perovskite photovoltaic devices is reviewed. Carbon nanomaterials allow precision tuning of their properties to serve as both electron- and hole-transporting material. Carbon nanomaterials facilitate an optimized charge balance, device stability, and efficiency.